Rights and human responsibilities: evolution of the concept (Revista LIDER, 2020)
Thesis defended in this text is that it is necessary now to unite duties and rights, such as personal, group, institutional responsibility and the State. To defend this idea are the approaches of Eastern cultures and thought of Thomas Scanlon, Johan Galtung and Amartya Sen are used. The first takes the justification of personal responsibility as a way to realize the justice, different attitude to the classic which examines fair institutions, without further reference to personal duties. It picks up Galtung thinking because of its reference to the current global governance and even if it criticizes the idea of human rights of Sen, the position of this author to gathers duties and rights.